Antimicrobial resistance of commensal Enterococcus faecalis and Enterococcus faecium from food-producing animals in Russia - Dmitry A. Makarov; Olga E. Ivanova; Anastasia V. Pomazkova; Maria A. Egoreva; Olga V. Prasolova; Sergey V. Lenev; Maria A. Gergel; Nataliya K. Bukova; Sergey Yu Karabanov (Veterinary World, 2022)
Background and Aim: Although Enterococcus faecalis and Enterococcus faecium are common members of human and animal gut microbiota, their resistance to different antimicrobials makes them important pathogens. Multidrug-resistant enterococci often contaminate foods of animal origin at slaughterhouses. The World Health Organization and the World Organization for Animal Health recommend including animal-derived enterococci in antimicrobial resistance (AMR) monitoring programs. This study aimed to fill a literature gap by determining the current AMR prevalence of E. faecalis and E. faecium from different food-producing animals in Russia.